Person, society, and value : towards a personalist concept of health - Taboada, Paulina; Cuddeback, Kateryna Fedoryka; Donohue-White, Patricia (Philosophy and medicine ;, 2002)
"Besides offering a critical analysis of the WHO definition and a review of both ancient and contemporary conceptions of health, the cooperative effort of physicians and philosophers presented in this book works through the challenges which any definition of health faces, if it is to be both truly personalist, and at the same time operational." "The overall purpose of this book is to capture the essentials of human health and to propose the outlines for a personalist understanding of this concept, i.e., a conception that does justice to the personal nature of human beings by introducing dimensions that are essential to personal life and well-being, such as the realms of rationality, affectivity and freedom, the realms of meaning, values, morality, and spirituality, the realms of social and interpersonal relations.".